2021
DOI: 10.1099/jmm.0.001341
|View full text |Cite
|
Sign up to set email alerts
|

An antipathogenic compound that targets the OxyR peroxide sensor in Pseudomonas aeruginosa

Abstract: Introduction. Antipathogenic or antivirulence strategy is to target a virulence pathway that is dispensable for growth, in the hope to mitigate the selection for drug resistance. Hypothesis/Gap Statment. Peroxide stress responses are one of the conserved virulence pathways in bacterial pathogens and thus good targets for antipathogenic strategy. Aim. This study aims to identify a new chemical compound that targets OxyR, the peroxide sensor req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The experimental inhibitor of OxyR that was reported in 2021 by Oh et al presented the first OxyR inhibition study that revealed selective antibacterial efficacy against P. aeruginosa. 51 We modified this inhibitor (Figure 1) with the addition of methyl oxo-enoate and HMK. As shown in Scheme 3, the Exp-1 inhibitor reacts in a concerted fashion comprising a single TS, leading to the product formation E-I.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental inhibitor of OxyR that was reported in 2021 by Oh et al presented the first OxyR inhibition study that revealed selective antibacterial efficacy against P. aeruginosa. 51 We modified this inhibitor (Figure 1) with the addition of methyl oxo-enoate and HMK. As shown in Scheme 3, the Exp-1 inhibitor reacts in a concerted fashion comprising a single TS, leading to the product formation E-I.…”
Section: Resultsmentioning
confidence: 99%
“…presented the first OxyR inhibition study that revealed selective antibacterial efficacy against P. aeruginosa . We modified this inhibitor (Figure ) with the addition of methyl oxo-enoate and HMK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among those virulence factors, the quorum-sensing systems are noteworthy, in that they are responsible for regulation of multiple virulence factors, involving the secreted chemicals called quormones, which could be targeted even without entry into the target pathogens [ 7 , 8 ]. Recently, we have identified a chemical hit to compromise the peroxide-sensor, OxyR through structure-based virtual screening [ 9 ] and developed an antipathogenic peptide that is derived from a phage protein targeting the bacterial motility and acute virulence [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%